An assessment of drinking-water quality post-Haiyan - Magtibay, Bonifacio; Anarna, Maria Sonabel; Fernando, Arturo (Western Pacific Surveillance and Response, 2015)
Introduction: Access to safe drinking-water is one of the most important public health concerns in an emergency setting. This descriptive study reports on an assessment of water quality in drinking-water supply systems in areas affected by Typhoon Haiyan immediately following and 10 months after the typhoon.Methods: Water quality testing and risk assessments of the drinking-water systems were conducted three weeks and 10 months post-Haiyan. Portable test kits were used to determine the presence of Escherichia coli and the level of residual chlorine in water samples. The level of risk was fed back to the water operators for their action.Results: Of the 121 water samples collected three weeks post-Haiyan, 44% were contaminated, while 65% (244/373) of samples were found positive for E. coli 10 months post-Haiyan. For the three components of drinking-water systems – source, storage and distribution – the proportions of contaminated systems were 70%, 67% and 57%, respectively, 10 months after Haiyan.Discussion: Vulnerability to faecal contamination was attributed to weak water safety programmes in the drinking-water supply systems. Poor water quality can be prevented or reduced by developing and implementing a water safety plan for the systems. This, in turn, will help prevent waterborne disease outbreaks caused by contaminated water post-disaster.